Taxonomic revision of the southern African Colletes fasciatus species group (Hymenoptera: Colletidae) - Zabel, Tina; Kuhlmann, Michael (European Journal of Taxonomy, 2023)
Fourteen new species of the Colletes fasciatus species group are described, all of them endemic to the winter rainfall area in South Africa: C. ascopalis sp. nov. ♀, C. carolinae sp. nov. ♀♂, C. cedarbergensis sp. nov. ♀, C. fabiani sp. nov. ♀♂, C. fuscitergus sp. nov. ♂, C. khoisanorum sp. nov. ♀, C. kogelbergensis sp. nov. ♀♂, C. littoralis sp. nov. ♀, C. longitarsus sp. nov. ♂, C. peerboomi sp. nov. ♀, C. richtersveldensis sp. nov. ♀, C. ruschia sp. nov. ♀♂, C. spinipes sp. nov. ♂, C. troetroeensis sp. nov. ♀. Two species are synonymized based on newly recognized sex associations: C. katharinae Kuhlmann, 2007 syn. nov. is synonymized with C. infracognitus Cockerell, 1937 and C. bokkeveldi Kuhlmann, 2007 syn. nov. with C. zygophyllum Kuhlmann, 2007. The previously unknown female of C. inornatus Cockerell, 1946 is described for the first time and new records of already described species are added. All of the currently known 37 species of the C. fasciatus-group are imaged and included in a key to facilitate their identification.